Tuva in the cultural dialogue: a comparative context - Popkov, Yuri Vladimirovich; Tyugashev, Evgeny Alexandrovich (The New Research of Tuva, 2020)
The article brings up the problem of cultural dialogue problem in global and regional aspects and focuses on the issue topical for comparative Tuvan studies – the one of positioning Tuva in the cultural dialogue within a comparative context. According to O. Spengler, culture can be seen as a separate social system in its specific historical peculiarity. This very concept allows us to discuss the culture’s ability of culture to enter and conduct a dialogue.We have reason to speak about the dialogue of cultures only if there is a meaningful and constructive exchange of speech and information going on. To engage in this, a culture has to be a speaking and non-silent one, and have the ability to speak not in monologues, but in dialogues. In its colloquial form, the culture has to be subject-oriented, attracted by the subjectness of another culture in its unique objective value.The comparative analysis of the situation traditional Tuvan culture finds itself in leads us to a number of conclusions. Firstly, by the criterion of openness to dialogue, it can be classified as a relatively closed culture. By the criterion of dialogue selectivity, Tuvans can be characterized as predominantly Asian-oriented; on the scale between “speaking” and “silent” cultures, Tuvan culture tends to be seen as silent, and it can be referred to as more monologue-like than dialogue-like.The current spread of contemporary networks and digitalization of public and personal life contribute to the changes in Tuva’s position in the cultural dialogue. At the same time, we believe that Tuvans will only benefit from cultivating a respectful and keen attitude to their own culture and from a better understanding of its details.
Keywords: Tuva; Tuvan culture; cultural dialogue; cross-cultural dialogue; cross-cultural communication; cross-cultural interaction; Uryankhai issue; Tuvan issue